Learning to Reach to Locations Encoded from Imaging Displays - Wu, Bing (2008)
The present study investigated how people learn to correct errors in actions directed toward cognitively encoded spatial locations. Subjects inserted a stylus to reach a hidden target localized by means of ultrasound imaging and portrayed with a scaled graph. As was found previously (Wu et al., 2005), subjects initially underestimated the target location but corrected their responses when given training with feedback. Three experiments were conducted to examine whether the error correction occurred at (1) the mapping from the input to a mental representation of target location; (2) the mapping from the representation of target location to the intended insertion response, or (3) the mapping from intended response to action. Experiment 1 and Experiment 3 disconfirmed Mappings 1 and 3, respectively, by showing that training did not alter independent measures of target localization or the action of aiming. Experiment 2 showed that the output of Mapping 2, the planned response -- measured as the initial insertion angle –was corrected over trials, and the correction magnitude predicted the response to a transfer stimulus with a new represented location.